2021
DOI: 10.1016/j.fct.2021.112276
|View full text |Cite
|
Sign up to set email alerts
|

Effect of processing smoked salmon on contaminant contents

Abstract: The influence of the type of smoking process (natural/liquid; hot/cold) and salt (NaCl or KCl) on the levels of polybrominated diphenyl ethers (PBDEs) and polycyclic aromatic hydrocarbons (PAHs) in smoked salmon was evaluated. One parent compound -BDE 47 -and two methoxylated forms -2′-MeO-BDE-68 and 6-MeO-BDE-47 -were detected in all the samples. Among the 14 PAHs analysed, naphthalene was the most abundant followed by phenanthrene and fluorene. Only smoked salmon treated with NaCl presented quantifiable leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
6
1
1
Order By: Relevance
“…No difference was observed for the benzo( a )pyrene content of the hot‐smoked tail fillet (0.07 ± 0.3 μg kg −1 ) and the liquid‐smoked fillet (0.05 ± 0.8 μg kg −1 ) ( P > 0.05) (data not reported). These results are different from the findings obtained in other studies reporting differences between hot and liquid smoking and concluding that the liquid smoke reduced the formation of PAHs in smoked salmon 42 . The benzo( a )pyrene content in smoked products depends, amongst other factors, on the smoking technology (degree, time, and temperature of smoking), mainly as a result of the method or condition of smoke generation, chemical composition of wood, and pyrolysis temperature (wood‐burning must be below 250 °C to reduce the carcinogenic compounds), which can explain the differences observed 43 .…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…No difference was observed for the benzo( a )pyrene content of the hot‐smoked tail fillet (0.07 ± 0.3 μg kg −1 ) and the liquid‐smoked fillet (0.05 ± 0.8 μg kg −1 ) ( P > 0.05) (data not reported). These results are different from the findings obtained in other studies reporting differences between hot and liquid smoking and concluding that the liquid smoke reduced the formation of PAHs in smoked salmon 42 . The benzo( a )pyrene content in smoked products depends, amongst other factors, on the smoking technology (degree, time, and temperature of smoking), mainly as a result of the method or condition of smoke generation, chemical composition of wood, and pyrolysis temperature (wood‐burning must be below 250 °C to reduce the carcinogenic compounds), which can explain the differences observed 43 .…”
Section: Resultscontrasting
confidence: 99%
“…These results are different from the findings obtained in other studies reporting differences between hot and liquid smoking and concluding that the liquid smoke reduced the formation of PAHs in smoked salmon. 42 The benzo(a)pyrene content in smoked products depends, amongst other factors, on the smoking technology (degree, time, and temperature of smoking), mainly as a result of the method or condition of smoke generation, chemical composition of wood, and pyrolysis temperature (wood-burning must be below 250 °C to reduce the carcinogenic compounds), which can explain the differences observed. 43 The benzo(a) pyrene concentration in smoked meat and fish should not exceed 1 μg kg −1 , which is considered as a maximum limit by legislation in some countries; therefore, the alligator fillets in the present study can be consumed with no harmful effects, regardless of the method used for smoking.…”
Section: Ph and A Wmentioning
confidence: 99%
“…Topus 2016 [ 31 ] demonstrated that salt and acetic acid concentration in the marinating process affected the physicochemical and sensory properties of marinated little tunny. The type of salt (NaCl or KCl) was also recently evaluated as a possible parameter that may influence contaminant levels in processed seafood [ 32 ]; the use of KCl instead of NaCl in smoked salmon processing resulted in lower levels of both polybrominated diphenyl ethers and polycyclic aromatic hydrocarbons. Despite these results, in this study salt was not considered, as its use is common in home-cooking procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, BaP is persistent organic pollutant, which poses a serious threat to global food security ( Średnicka et al, 2021 ). Seafood with increasing BaP content increases the risk of cancer ( Wang et al, 2020 ) and BaP in roast meat, smoked meat and fried foods will cause serious damage to animals and human organs, such as the liver and kidneys ( Takeshita and kanaly, 2019 ; Iko Afé et al, 2020 ; Cunha et al, 2021 ; Goedtke et al, 2021 ; Mertens et al, 2021 ; Ge et al, 2022 ). Very recent studies ( Kostoff et al, 2020 ) have indicated that people exposed to increased levels of BaP will lead to degradation or dysfunction of the immune system and people will become more susceptible to 2019-nCoV.…”
Section: Introductionmentioning
confidence: 99%